Validitas Pengembangan Buku Ilmiah Populer Berkearifan Lokal tentang Pengaruh Tingkat Konsentrasi Kunyit terhadap Mutu Bekasam Ikan Papuyu (Anabas testudineus) - Hadijah Hadijah; Khairunnisa Khairunnisa (Celebes Science Education, 2023)
The local wisdom food product industry is increasingly developing, one of which is bekasam. Bekasam is a fermented product that is applied to fish to produce a distinctive taste and aroma. Information about this needs to be known by the general public and learners such as students in the form of teaching materials. Therefore, it is very necessary to develop interesting teaching materials such as popular scientific books (BIP) in order to provide knowledge about the importance of besam fermentation products. The aim of this research is to describe the validity of a popular scientific book based on local wisdom about the effect of turmeric concentration levels on the quality of papuyu fish (Anabas testudineus) tamarind. This research uses the Educational Development Research (EDR) type of research with the Plomp design method which is limited to the prototype development stage (Prototyping phase) in the self-evaluation and expert review steps. Research data was obtained from validity instruments. The research results were obtained from the validity of the BIP by experts with an average percentage of 87.97% with a very valid category. These results prove that BIP can be used as additional teaching material that can increase students' understanding of the topic of fermentation.